Decision on the admissibility of criminal complaints in the Brazilian Superior Court of Justice: a quali-quantitative research - João Henrique de Andrade; Nestor Eduardo Araruna Santiago; Uinie Caminha (Revista Brasileira de Direito Processual Penal, 2021)
This is an analysis of the discourse of the Brazilian Superior Court of Justice (STJ) in relation to the judgment confirming the admissibility of the criminal prosecution. It seeks to understand whether the STJ's jurisprudence finds an echo in the constitutional text regarding the need to substantiate judicial decisions. 107 of them were raised in the interstice from 2008 to 2019, after the enactment of Law no. 11,719/2008. We intended to understand the evolution in the jurisprudential comprehension on the need to justify the decision whether to admit or not the criminal prosecution. The methodology used is both quantitative and qualitative. The study points out that the STJ has been presenting an inadequate response to the constitutional text, since the admissibility judgment as a judicial decision requires a justification in the light of article 93, IX, of the Brazilian Federal Constitution and of article 315 of the Criminal Procedure Code.